The Role of DNMT Methyltransferases and TET Dioxygenases in the Maintenance of the DNA Methylation Level - Anastasiia T. Davletgildeeva; Nikita A. Kuznetsov (Biomolecules)
This review deals with the functional characteristics and biological roles of enzymes participating in DNA methylation and demethylation as key factors in epigenetic regulation of gene expression. The set of enzymes that carry out such processes in human cells is limited to representatives of two families, namely DNMT (DNA methyltransferases) and TET (DNA dioxygenases). The review presents detailed information known today about each functionally important member of these families and describes the catalytic activity and roles in the mammalian body while also providing examples of dysregulation of the expression and/or activity of these enzymes in conjunction with the development of some human disorders, including cancers, neurodegenerative diseases, and developmental pathologies. By combining the up-to-date information on the dysfunction of various enzymes that control the DNA “methylome” in the human body, we hope not only to draw attention to the importance of the maintenance of a required DNA methylation level (ensuring epigenetic regulation of gene expression and normal functioning of the entire body) but also to help identify new targets for directed control over the activity of the enzymes that implement the balance between processes of DNA methylation and demethylation.